Iron-mediated oxidative stress induces PD-L1 expression via activation of c-Myc in lung adenocarcinoma - Battaglia, Anna Martina; Sacco, Alessandro; Aversa, Ilenia; Santamaria, Gianluca; Palmieri, Camillo; Botta, Cirino; De Stefano, Roberto; Bitetto, Maurizio; Petriaggi, Lavinia; Giorgio, Emanuele; Faniello, Concetta Maria; Costanzo, Francesco; et al. (Frontiers in Cell and Developmental Biology, 2023)
The PD-1/PD-L1 axis is hijacked by lung adenocarcinoma (LUAD) cells to escape immune surveillance. PD-L1 expression in LUAD is affected, among others, by the metabolic trafficking between tumor cells and the tumor microenvironment (TME). In this study, we highlight a significant correlation between iron density within the TME and PD-L1 expression in 16 LUAD tissue specimens. In agreement, we show that a more pronounced innate iron-addicted phenotype, indicated by a higher transferrin receptor CD71 levels, significantly correlates with higher PD-L1 mRNA expression levels in LUAD dataset obtained from TCGA database. In vitro, we demonstrate that the addition of Fe3+ within the culture media promotes the significant overexpression of PD-L1 in A549 and H460 LUAD cells, through the modulation of its gene transcription mediated by c-Myc. The effects of iron lean on its redox activity since PD-L1 up-regulation is counteracted by treatment with the antioxidant compound trolox. When LUAD cells are co-cultured with CD3/CD28-stimulated T cells in an iron-rich culture condition, PD-L1 up-regulation causes the inhibition of T-lymphocytes activity, as demonstrated by the significant reduction of IFN-γ release. Overall, in this study we demonstrate that iron abundance within the TME may enhance PD-L1 expression in LUAD and, thus, open the way for the identification of possible combinatorial strategies that take into account the iron levels within the TME to improve the outcomes of LUAD patients treated with anti-PD-1/PD-L1-based therapies.